Afina Batik's Strategy in the Laweyan Batik Village Area in Realizing the Cleaner Production Concept - Fathoni Firmansyah; Siti Rachmawati; Fikri Fadly Arkasala; Angelina Novia Defatima; Arief Putra Ajie Wicaksono; Arrafi Tegar Wibisono; Edbert Lintang Panoto Nagari Satrio; Jashinta Anggi Pebriane Sitepu (International Journal of Engineering Education, 2022)
Cleaner production is an environmental management effort through preventive strategies to prevent pollution and waste of materials before the pollution occurs which is carried out in a sustainable manner in the hope of reducing the negative impact of the activities carried out. The view in cleaner production itself will provide a different perspective to achieve and sustainable consumption with the value of the resources that have been used. However, so far the batik production process is still considered inefficient and environmentally friendly. Thus, this study aims to determine the process of making batik and the behavior of efficiency in the batik production process in Afina Batik’s MSME. This research was conducted by observation and interviews. Interviews were conducted using purposive sampling method. Then, given solutions related to the management of Afina Batik to go to cleaner production. The interviewees included the flow of the batik production process, the raw materials used, the use of energy in batik production, both water and electricity, the use of chemicals, the type of waste generated and the amount, and the waste treatment process. The results obtained are various wastes from the dyeing process to washing. In addition, several factors were found that hinder Afina Batik from moving towards a cleaner production process, such as the use of synthetic dyes, still using cordwood, and still wasteful use of air. There are several methods that can be used to implement cleaner production at Afina Batik’ MSME, namely by maximizing the use of candles to efficient use of energy, air, and raw materials.